Preschoolers’ Use of Requests - Emel Uçar; Özden Akyol Bal (Dilbilim Araştırmaları Dergisi)
Request situations are of great value to observe multiple variables such as power, distance and imposition of the request on the hearer to get the desired object or action. This study investigated requests of Turkish monolingual preschoolers in terms of Blum-Kulka and Olshtain’s (1984) categories. The aim was to find out the structures of head act and adjunct(s), the directness level of the strategy types and perspectives of the speakers (hearer oriented, speaker oriented, hearer and speaker oriented, and impersonal) used in requests. Data was gathered from 24 Turkish speaking children aged between 4;5 and 5;6, 13 of whom were girls and 11 were boys. To collect data, four situations were created considering power and level of imposition of the requests, namely Low Power-Low Imposition, Low Power-High Imposition, High Power-Low Imposition, and High Power-High Imposition. The results showed that 1) children used head act most frequently in their requests, 2) children mainly used direct requests, 3) children preferred to use speaker oriented perspective more than the other request perspectives. In addition to the categories provided by Blum-Kulka and Olshtain (1984), a ‘nonverbal’ category was added which was observed to be peculiar to children. However, results were interpreted cautiously since they displayed varieties for each case due to the nature of the activities.